Mathematic Supplementary Development on Title of Division, Addition, Subtraction, Multiplication and Decimal for Prathomsuksa 6 Students - Lawthongkum, Anawach; Khunno, Chinakorn; Samakhom, Lamai; Khomobklang, Sirichai; Suksakunee, Jantanee (Interdisciplinary Academic and Research Journal, 2023)
Mathematics is the science of arithmetic and plays a very important role in developing human thinking potential, enabling creativity, rational thinking, orderly and methodical thinking, able to analyze problems and situations carefully and make plans, decisions, and solve problems properly. This study aims to study the development and the achievement of Mathematic supplementary development on the title of division, addition, subtraction, multiplication, and decimal for Prathomsuksa 6 students. The target group was 29 Prathomsuksa 6 students, semester 1 of the academic year of 2565 with One-Group Posttest Design. The instruments were 12 sets of Mathematic supplementary on the title of division, addition, subtraction, multiplication, and decimal for Prathomsuksa 6 students, the 40 items of achievement test with the difficulty score at 0.35 – 0.74, the discrimination score at 0.36 – 0.77, the reliability score at.94 The statistical procedures employed to examine the data were Percentages. Results of the study were the following: (1) Mathematic supplementary development on the title of Division, addition, subtraction, multiplication, and decimal for Prathomsuksa 6 students indicated a proficiency score of E1/E2 at 86.44/85.22. (2) The achievement of learning with Mathematic supplementary development on the title of division, addition, subtraction, multiplication, and decimal for Prathomsuksa 6 students indicated 85.52% above the criteria determination.